Determinants of Financial Performance with Sustainability Report as A Moderation Variable - Permana, Tista Fadhil; Djuharni, Darti; Arniati, Tutik (International Journal Administration, Business & Organization, 2025)
This study aims to determine the effect of green accounting, environmental performance, and environmental costs on the level of profitability of financial performance moderated by sustainability report. This research is quantitative in the type of causality, with a research population of 80 manufacturing companies’ industrial classification based on production results for the 2020-2022 period and determination of the number of samples of 20 companies obtained through purposive sampling techniques. Data collection was carried out using secondary data tracing through the Indonesia Stock Exchange and the GRI G4 index of each company. Data processing using SPSS software program is analyzed with a multiple linear regression analysis approach Moderated Regression Analysis (MRA). Based on the results of the study shows that green accounting, environmental performance, and environmental costs do not have a significant effect on financial performance